Analyzıng the Impact of Knowledge Sharıng in Vırtual Teams: Practıcal Evıdence from Indonesıa Open Unıversıty - Yusriani, Sri; Patiro, Shine Pintor Siolemba; Rekarti, Endi; Pamungkas, Charisma Rahmat; Nurbaeti, Nunung (Yayasan Ilomata, 2024)
Remote studying and working pose challenges to personal development. In this environment, knowledge sharing is essential for improvement and serves as a vital organizational tool. However, many Open University students remain unaware of the benefits derived from active engagement in Virtual Teams. This research examines the impact of knowledge sharing and skill application in virtual team sessions, focusing on the Master of Management program at the Indonesia Open University. A qualitative method through Focus Group Discussions (FGDs) with 40 'the Ready to Contribute' (Siap Berkarya) participants was employed. Key themes identified include leadership effectiveness, digital culture assimilation, self-efficacy, work-life balance, and the potential evolution of human resource management. The study underscores the importance of transparent communication, mutual trust, and effective coordination for virtual team functionality. It contributes to organizational policy development, emphasizes digital well-being's significance in today's digital age, and enhances understanding of virtual teams' complex dynamics.